Outcomes of intensity‐modulated radiotherapy as primary treatment for oropharyngeal squamous cell carcinoma – a European singleinstitution analysis. (19th June 2016) - Bird, T.; De Felice, F.; Michaelidou, A.; Thavaraj, S.; Jeannon, J.–P.; Lyons, A.; Oakley, R.; Simo, R.; Lei, M.; Guerrero Urbano, T.
Abstract : Objectives: To analyse survival and toxicity outcomes in patients treated with primary intensity‐modulated radiotherapy (IMRT) for oropharyngeal squamous cell carcinoma (OPSCC) in the era of routine human papilloma virus (HPV) testing. Design: Single‐institution case series. Setting: Tertiary Head and Neck Cancer Unit. Participants: A total of 186 patients received IMRT (+/− chemotherapy) for radical primary treatment of OPSCC between March 2010 and December 2013. HPV status was available for 88% of cases. Median radiation dose was 65 Gy in 30 daily fractions. 90% of stage III/IV patients received concurrent chemotherapy or cetuximab. Main Outcome Measures: Overall, disease‐free and disease‐specific survival; rates of late xerostomia and dysphagia. Results: A total of 177 patients completed treatment (Stage I/II: 23; Stage III/IV: 154), with median follow‐up of 26 months. Estimated 3‐year overall survival (OS), disease‐free survival (DFS) and disease‐specific survival (DSS) rates were 77.2% (70.5–83.9), 72.3% (65.4–79.2) and 80.2% (74.1–86.3). Estimated 3‐year OS, DFS and DSS for HPV‐positive patients were 90.9% (85.2–96.6), 87.9% (81.4–94.4) and 91.8% (86.3–97.3). A previously identified risk stratification method was validated, showing improved OS for low‐risk over high‐risk patients (HR 0.09, P < 0.001). The 2‐year feeding tube retention rate was 6%, and 2‐year grade ≥2 xerostomia rate was 38% (23% if mean contralateral parotid dose <24 Gy). Conclusions: Outcomes with IMRT are favourable, particularly in the HPV‐positive patient group. This data further supports the use of a previously described prognostication model that can be used to select patients for escalation/de‐escalation clinical trials.